2019
DOI: 10.1080/13504851.2019.1696449
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effects of inequality on economic growth in the US states: the role of human capital to physical capital ratio

Abstract: Theory suggests that the effect of inequality on growth varies with the level of economic development, as captured by the ratio of human capital to physical capital. In particular, the effect is shown to be positive at lower levels of this ratio, and turns negative beyond a threshold in such models. Using a comprehensive panel of annual data for the 48 contiguous US states over the period 1948 to 2014, we find overwhelming evidence in support of this theory, unlike prior work on this topic. Hence, our paper hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As health investment may crowd out physical capital investment and affect the accumulation of physical capital, Gong et al ( 34 ) found that excessive investment in health may have a negative impact on economic growth. Çepni et al ( 35 ) proved that the effect of human capital on economic growth is positive when the ratio of human capital to material capital is low, whereas if it exceeds a threshold, the effect becomes negative. Zhang et al ( 36 ) also pointed out the existence of this threshold effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As health investment may crowd out physical capital investment and affect the accumulation of physical capital, Gong et al ( 34 ) found that excessive investment in health may have a negative impact on economic growth. Çepni et al ( 35 ) proved that the effect of human capital on economic growth is positive when the ratio of human capital to material capital is low, whereas if it exceeds a threshold, the effect becomes negative. Zhang et al ( 36 ) also pointed out the existence of this threshold effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their model suggests that inequality impacts growth positively below a certain threshold of the human to physical capital ratio, beyond which the effect is negative. Bhatti, Haque and Osborn (2015) and Çepni, Gupta and Lv (2020) test and validate Galor and Moav's model. Chen (2003) intuitively postulates an inverted U-shaped relationship between initial income distribution and long-term economic growth, and an estimation and test of this relationship using cross-country data confirms the proposition which is also reminiscent of Kuznets's (1966) inverted U-shaped curve.…”
mentioning
confidence: 99%